Efektivitas LKPD Materi Penyajian Data Berbasis Lectora Inspire Dengan Pendekatan CTL Di Sekolah Dasar - Niza, Ainun; Ariani, Yetti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of the study was to see the effectiveness of worksheets in the presentation material of lectora inspire-based data with contextual tecahing and learning approaches to learning outcomes of students in grade IV SD Plus Marhamah, Padang City. This study uses a quantitative approach in the form of pre-experimental, one group research design pretest-posttest design, Purposive Sampling sampling technique, namely 22 students in the experimental class. The results of the study show that the experimental class students after using the worksheet on the presentation material of lectora inspire-based data with contextual tecahing and learning approach have a higher average value than the students before using the worksheet of students presenting lectora inspire-based data with a contextual approach tecahing and learning. In testing the hypothesis, the results obtained using the T-Test technique obtained tcount 5.98> ttable 2.07, at a significance level of 0.05.